PREDIKSI HARGA SAHAM DENGAN MENGGUNAKAN JST (JARINGAN SYARAF TIRUAN) - Leonardy Khanady (JURNAL ILMIAH INFORMATIKA, 2019)
Stock trading is one of the very high risk investments and if not analyzed in detail, it will experience huge losses and bring absolute errors. By carrying out careful analysis and accurate predictions, it will bring high prospects and ease in determining policies to achieve high profits in the world of stocks. In this study, stock price predictions will be investigated by using RapidMiner Studio software using the Artificial Neural Network method. The results of the study will prove that using artificial neural networks can predict the price of a stock whose price is very close to the actual price with a very small MSE value.